Guttiferones K and L, Antiproliferative Compounds of Rheedia calcicola from the Madagascar Rain Forest - Cao, Shugeng (2007)
Bioassay-guided fractionation of the ethanol extract obtained from the fruits of Rheedia calcicola led to the isolation of two new guttiferone analogues, guttiferones K (1) and L (16-hydroxyguttiferone K) (2). The structures of 1 and 2 were established on the basis of extensive interpretation of one and two dimensional NMR spectroscopic data. Both compounds were tested for their antiproliferative activity against the A2780 human ovarian cancer cell line.